1995
DOI: 10.2307/3665559
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Risk Sensitivity and Its Determinants: A Firm and Industry Analysis of U.S. Multinationals

Abstract: We develop a model of firm valuation to examine the exchange risk sensitivity of 409 U.S. multinational firms during the 1978-89 period. In contrast to previous studies, we find that exchange rate fluctuations do affect firm value. More specifically, we find that approximately sixty percent of firms with significant exchange risk exposure gain from a depreciation of the dollar. We also find that cross-sectional differences in exchange risk sensitivity are linked to key firm-specific operational variables (i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
211
1
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(232 citation statements)
references
References 20 publications
13
211
1
2
Order By: Relevance
“…They find only limited evidence of exposure faced by industries in the three economies, reporting that only 11 out 39 U.S. industries face significant exposure with only 4 out 19 industries in Canada although there are 7 out of 20 in Japan. Additionally, Choi and Prasad (1995) find only limited evidence of exposure with only 15% of U.S. firms having a significant coefficient. Khoo (1994) investigates the level of exposure to exchange rates of mining firms in Australia.…”
Section: Introductionmentioning
confidence: 85%
“…They find only limited evidence of exposure faced by industries in the three economies, reporting that only 11 out 39 U.S. industries face significant exposure with only 4 out 19 industries in Canada although there are 7 out of 20 in Japan. Additionally, Choi and Prasad (1995) find only limited evidence of exposure with only 15% of U.S. firms having a significant coefficient. Khoo (1994) investigates the level of exposure to exchange rates of mining firms in Australia.…”
Section: Introductionmentioning
confidence: 85%
“…Likewise, Amihud (1994) does not succeed too even after using for his sample, 32 companies listed in the Fortune magazine's "50 Leading Exporters" list. Bodnar and Gentry (1993), in a multi-country study, find that 21% to 25% of the firms in USA, Japan and Canada display an exposure to exchange rate changes, percentage significantly higher than the ones obtained by Choi and Prasad (1995) who used an American dollar index for their US multinational firms: 14.9% at the firm level and 10% at the industry level.…”
mentioning
confidence: 72%
“…Again, the results were not very different as for example Choi and Prasad (1995) and Choi et al (1998). Nevertheless some authors using the orthogonalized model succeeded in obtaining better results, as did Glaum et al (1998) Exposure may be a complex concept to measure, especially if we take into account the time the firm needs to adjust its financial management to exchange rate fluctuations or the fact that company information is only disclosed at regular moments in the year hence the time also needed by the market to adjust its valuation process.…”
mentioning
confidence: 93%
“…This risk is caused by the unpredictable movements of exchange rates and the effect of exchange rates on company performance. For example, many studies, such as Jorion (1990), Agarwal and Ramaswami (1992), Bodnar and Gentry (1993), Amihud (1994), Choi and Prasad (1995), Donnelly and Sheehy (1996), He andNg (1998), Miller andReuer (1998), Hagelin and Prambourg (2004) and Clark and Mefteh (2011) to mention only a few, documented the effect of exchange rate fluctuations on firm performance and the firm's risk profile. 5 Pesaran et al (2006) showed that severe fluctuations in exchange rates may significantly affect the companies' balance sheets, particularly international ones, and increase their default risk.…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%